Epidemiology and mortality in bacterial bloodstream infections in patients with hematologic malignancies - Duygu Mert; Sabahat Ceken; Gulsen Iskender; Dicle Iskender; Alparslan Merdin; Fazilet Duygu; Mustafa Ertek; Fevzi Altuntas (Journal of Infection in Developing Countries)
Introduction: Patients with hematological malignancies, who are in the high risk group for infectious complications and bacterial bloodstream infections. The aim of the study evaluated epidemiology and mortality in bacterial bloodstream infections in patients with hematologic malignancies. In addition to determine the risk factors, changes in the distribution and frequency of isolated bacterias.